PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA CV. BUNGA PADI DI KABUPATEN CIANJUR : Manajemen Pemasaran - RULLY MOCH. ICHSAN, SS., MM Rully (Ekonomedia, 2026)
The purpose of this study is to examine how pricing and marketing affect consumers' decisions to buy at CV. Rice Flowers in Cianjur Regency. The particular goals are to evaluate the substantial influence of price on consumer purchase decisions and ensure if promotions have a considerable impact on such decisions. The combined impact of pricing and marketing on decisions to buy at CV. Rice Flowers in Cianjur Regency is another goal of this study. Using a random sample approach, questionnaires were given to CV. Rice Flower customers in order to gather the data used in this study. Validity tests, reliability tests, correlation tests, regression tests, classical assumption tests, and determination tests were used to analysed the data. According to the study findings, the first hypothesis is accepted since the t-count value for promotion is 3.330 > t-table 1.974 and the significance value is 0.001 < 0.05. With a significant value of 0.001 < 0.05 and a t-count value for price of 3.999 > t-table 1.974, the second hypothesis is also approved. The third hypothesis is also accepted in the simultaneous test, as indicated by the F-count value of 20.956 > F-table 3.05 and the significance value of 0.001 < 0.05. The resulting multiple linear regression equation, Y = 20.225 + 0.253X₁ + 0.284X₂, indicates that for every 1% rise in the price and promotion variables, there will be a corresponding 0.253 and 0.284 increase in purchase choices